Kaempferia parviflora Extract (SIRTMAX®) reduces body fat in adults who are overweight: a 12-week randomized, double-blind, placebo-controlled trial - Sung, Hyun Kyung; Kim, Jinhak; Oh, Dongchan; Eun, Sang Won; Tatsuzaki, Jin; Shin, Seon Mi; Jeong, Su Hyeon (Frontiers in Nutrition, 2025)
Background/objectivesKaempferia parviflora Extract (SIRTMAX®) has been reported to alleviate obesity. However, few studies have investigated this topic and none have evaluated its potential among Koreans. Therefore, we aimed to evaluate the efficacy of K. parviflora extract in body fat reduction among Korean adults.MethodsIn total, 108 individuals were screened and randomly assigned to the intervention and control groups, and the results of 83 participants were analyzed. Changes from baseline (when the consumption of test and control foods commenced) to the end of the 12th week, were compared. The primary endpoints were body fat mass and body fat percentage changes, measured using dual-energy X-ray absorptiometry. The secondary endpoints were changes in (1) lean body mass; (2) total fat area, subcutaneous fat area, visceral fat area, and visceral subcutaneous fat ratio; (3) body weight, body mass index, waist circumference, hip circumference, and waist-to-hip circumference ratio; (4) serum total cholesterol, low-density lipoprotein cholesterol, triglyceride, high-density lipoprotein cholesterol, leptin, and adiponectin; (5) and body fat mass, body fat percentage, and lean body mass by region (arms, legs, trunk, android, and gynoid).ResultsAfter 12 weeks, body fat, body weight, and body mass index significantly reduced in the intervention group compared with the control group. Similar findings were observed for total fat area, subcutaneous fat area, visceral fat area, and visceral subcutaneous fat ratio. However, no significant difference was observed in waist and hip circumference values. Additionally, the intervention food was determined to be safe.ConclusionThis study suggests that health functional foods are effective in reducing body fat, thereby preventing various obesity-related diseases and metabolic syndromes.